EXPERIMENTAL RESEARCH OF DIRIGIBILITY AND HAULING INDEXES OF THE 14 КН CLASS TRACTOR ON THE PLOUGHING - Харак, Р. М.; Левчук, В. І.; Лихвенко, С. П. (Scientific Progress & Innovations, 2015)
The results of experimental research of dirigibility, hauling and economic indexes of arable aggregate in composition the tractor of MTZ-50 with the plough of PN 3-35B on stubble with the differential and blocked interwheeled drive of back bridge are presented. As a result of analysis of research results worsening of dirigibility of tractor is set at the blocked drive comparatively with a differential. At the same time, the considerable diminishing of skidding and increase of aggregate hauling efficiency (about 10 %) at the blocked drive were noticed. Researches of tractor are conducted also by hauling recommendation at motion in a furrow depth 30 cm (right wheels) and on stubble (left wheels) on III, IV and the V transmissions. The results allow to draw a conclusion about the substantial improvement of hauling indexes of tractor with the blocked interwheeled drive.